2019
DOI: 10.1016/j.chb.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Why do people play location-based augmented reality games: A study on Pokémon GO

Abstract: Pokémon GO brought the location-based augmented reality games into the mainstream. To understand why people play these games, we created an online survey (n=2612) with open questions about the reasons to start, continue, and quit playing Pokémon GO, and composed categories of the answers through a thematic analysis. Earlier experiences especially with the same franchise, social influence, and popularity were the most common reasons to adopt the game, while progressing in the game was the most frequently report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 18 publications
5
68
0
Order By: Relevance
“…Furthermore, the game has also been characterized as a highly useful channel for uniting young as well as the older generation in outdoor activities. 1 During the first 6 months of its launch, the game has also set a number of records including fastest game to be at the top of the charts in the App Store and Google Play. 2 Pokémon Go has also been the most downloaded game (and application) during the first week on the App Store.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the game has also been characterized as a highly useful channel for uniting young as well as the older generation in outdoor activities. 1 During the first 6 months of its launch, the game has also set a number of records including fastest game to be at the top of the charts in the App Store and Google Play. 2 Pokémon Go has also been the most downloaded game (and application) during the first week on the App Store.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, features such as physical activation, outdoor exploration, social interactivity, and health benefits that accrue from those activities, as well as privacy and trust issues that arise due to location and collaboration, are hallmarks of this new gaming genre. While there is a plethora of research on various motives associated with games [24,37,58,65], negative gaming outcomes [11,12,34], demographic variations [9,20,21,57], and gamers behaviors on specific games [12,17,28,35], the novelty and rapid popularity of location-based augmented reality games (particularly Pokémon Go) across the highly diverse global audience provides an opportunity to revisit many of the core issues and findings of gaming research [1,10,23,38].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a similar rush of interest by researchers, as over the past years close to 10,000 academic publications have been written from various perspectives (Google Scholar, search phrase 'Pokémon GO'). Although the game elements that encourage exploration are key reasons for continued Pokémon GO gameplay (Alha et al 2019). Pokémon GO also has social implications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This player base and its behaviour offers rich pool of material for analysing game context and blending of realities during gameplay of LBMGs. Although Pokémon GO can be characterised as an 'an augmented reality (AR) game', the AR feature is not extensively used or is seldom required in gameplay (Alha et al 2019;Azuma 1997;Paavilainen et al 2017). The blending of game's digital contents augments the physical environment in a way that the game can be characterised as a pervasive game, more specifically a mixed reality or a hybrid reality game in addition to being an LBMG (Benford and Giannachi 2011;Montola, Stenros, and Waern 2009;de Souza e Silva 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When studying consumer behavior and influencing factors, researchers mostly study from the micro perspective and rarely study from the macro perspective. Alha et al [23] found that the player's personal situation outside the game and playability problems were the most significant reasons to quit the game. Huang [24] found that affective involvement showed the greatest influence on purchase intention compared to flow and cognitive involvement.…”
Section: Research Perspectivementioning
confidence: 99%